Durabilitas Beton Bubuk Kulit Kerang Di Lingkungan Air Laut - Elen Tarisa; Monita Olivia; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In this study,blood clam used as cement replacement material. The specimens were cured in distilled water until 28 days. Then specimens were immersed in sodium chloride solution until 91 days. The parameters studied include compressive strength, workability, and density. These properties were compared with those of a control concrete that was made of Ordinary Portland Cement (OPC). The main parameter of this study was the proportion of waste blood clam (4% by cement weight).Keywords: blood clam, cement replacement, sodium chloride solution, compressive strength, workability, density